Long-Term Contracts and Asset Specificity Revisited: An Empirical Analysis of Producer-Importer Relations in the Natural Gas Industry - Anne Neumann; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this paper, we analyze structural changes in long-term contracts in the international trade of natural gas. Using a unique data set of 262 long-term contracts between natural gas producers and importers, we estimate the impact of different institutional, structural and technical variables on the duration of contracts. We find that contract duration decreases as the market structure of the industry develops to more competitive regimes. Our main finding is that contracts that are linked to an asset specific investment are on average four years longer than those who are not.
Keywords: 330; asset specificity; econometric analysis; long-term contracts; natural gas